Cura pastoralis w świetle eklezjologii pastoralnej ks. Franciszka Blachnickiego - Biela, Bogdan (Studia Pastoralne, 2005)
On 21st of November 2004 is 40 anniversary of announcing a dogmatic konstitution about Church Lumen gentium, which endeepening the reflection of Church mistery shows at the same time a base of aftercouncil conception of religious service. It implicates at the same time new understanding of meaning „service”, more often expressed by latin cura pastoralis instead of cura animarum. This is the way as father Blachnicki understood religious service. He in his scientifical work and charizmatical intuition undobtfuly foreheaded his epoch, becoming a special kind of prophetic lumen of assimilation and realization of teaching Vaticanum II. Fr. Blachnicki endeepening ecclesilogy of Vaticanum II and works of contemporary to him theologians discovered that an expression koinonia, shows as one of accepting in ecclesiology a very rich reality under the name „Church”. That „new picture of Church” became so precious, as it could become a leading picture for pastoral theology and religious service, expressing at the same time purpose, subject, aims and methods cura pastoralis of Church. Basing on new vision of Church, the autor of ecclesiological deduction of pastoral theology formulated a principle in a way of acting in the Church: „Church salvation intercession (means religious service), should be celebrated in this purpose and in this way to realisation selfgiving God in Christ in word, sacrament and to condition free receiving in together giving in Holy Spirit through faith and love, for personification the community in vertical (with God) and horisontal (with brothers) in visual and effective sign of eucharistic gathering, and a local community in unity with common Church”. Analising theological – pastoral work of fr. Blachnicki, one can state that he reviewed and improved till the end of his life ecclesiological conception of pastoral theology, verifing at the same time his thoughts in practice in Light – Life Movement of a living Church as its founder. He has even suggested a neccessity of creating pneumatological – Christological – ecclesiological tractat of pastoral theology, where a pneumatological vision of Church would be appreciated. That is why one of servant of God suggestion was a proposal to go from service to evangelization. He named it a Copernican turn. In that state it is possible to lead a whole and organic conception cura pastoralis, understood as a proccess of building a Church in local community. Reality of Church starts from evangelisation, which iniciates liberation procceses of people and given environment. Next step is to endeep – by catechumenal formation – to life in ecclesial community (martyria, leiturgia, diakonia). That is why a main conclusion coming from the fact that Church realised in concret, local communities is for fr. Blachnicki a postulate to rebuild a whole religious service so it would serve the formation of basic communities of christian life in parishes. So it is neccessary to leadin a model of parishal community. To solve this dilemma; how to lead a model of postcouncil parish in life as one cannot build a living community without existing adult ecclessiological communities, the founder of Light – Life Movement showed a part and a chance in contemporary life for different movements based on a whole and catechumenal formation. Fr. Blachnicki realised at the same time that composing model of realisation a parish as a community in Light – Life Movement has a fundamental influence on a style of work and priests life.